2016
DOI: 10.1007/s12665-016-6092-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of microorganisms and enzymes to soil contamination with a mixture of pethoxamid terbuthylazine

Abstract: This study analysed the effect of a mixture of pethoxamid (P) and terbuthylazine (T) contained in the herbicide Successor T 550 SE on organotrophic bacteria, total oligotrophic bacteria, Azotobacter and actinomycetes, oligotrophic sporulating bacteria, fungi and on the activities of dehydrogenases, catalase, urease, alkaline phosphatase, acid phosphatase, arylsulphatase and bglucosidase. The phytotoxic effect of this pesticide on maize was also determined. The study was undertaken because of a lack of data con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…However, Borowik et al (2017) and Kacynski et al (2016) have reported that mesotrione applied in herbicide mixtures of mesotrione + terbuthylazine + S-metolachlor and mesotrione + S-metolachlor inhibit DHA when the herbicides are applied at doses higher than the recommended field rate. It has been reported accordingly that the application of herbicides mixtures to soil can inhibit DHA (Kacynski et al, 2016;Wyszkowska et al, 2016).…”
Section: Soil Dehydrogenase Activity (Dha)mentioning
confidence: 99%
“…However, Borowik et al (2017) and Kacynski et al (2016) have reported that mesotrione applied in herbicide mixtures of mesotrione + terbuthylazine + S-metolachlor and mesotrione + S-metolachlor inhibit DHA when the herbicides are applied at doses higher than the recommended field rate. It has been reported accordingly that the application of herbicides mixtures to soil can inhibit DHA (Kacynski et al, 2016;Wyszkowska et al, 2016).…”
Section: Soil Dehydrogenase Activity (Dha)mentioning
confidence: 99%
“…4B, C). In similar studies, a negative effect on the structure of microorganisms affecting Actinobacteria was stated after the application of a mixture of pethoxamid and terbuthylazine (Wyszkowska et al, 2016). Also, it has been indicated a significant early impact and a relevant late impact on the bacterial community when the application of pethoxamid and glyphosate to soil was carried out (Valverde et al, 2014).…”
Section: Phospholipid Fatty Acid Profile Analysismentioning
confidence: 84%
“…The most significant effect was a DHA peak value observed after the herbicide's application at the rate of 50 mg kg -1 in S+GC. Wyszkowska et al (2016) have reported a strong inhibition of soil DHA when a mixture of pethoxamid and terbuthylazine is applied at rates higher than 14.63 mg a.i. kg -1 soil, regardless of the length of the assay.…”
Section: Soil Dehydrogenase Activitymentioning
confidence: 99%
“…Oligotrophic microorganisms including many bacteria and fungi grow in extremely nutritionally-deficient environments in which the concentrations of organic substances are low (Wyszkowska et al 2016). As shown in Fig.…”
Section: Confirmation That H Latericoloratus Cgmcc 16346 Is Oligotromentioning
confidence: 99%